Remoção do corante Azul Reativo 5G utilizando o adsorvente comercial Dowex Optipore SD-2 - Oliveira, Silvia Priscila Dias de (2013)
In this work, removal of Reactive Blue 5G dye using a commercial Dowex Optipore SD-2 adsorbent was investigated regarding variations on pH (1-12), temperature (20-50oC) and shaking (90-200 rpm) values in order to establish best adsorption conditions. The point of zero charge (pcz) was determined varying solution pH from 2 to 12 and defining the pH range where the adsorbent surface is electrically neutral. Batch kinetic experiments at pH 2 consisting on a mixture of 5 mg adsorbent and 50 mL dye solution (150 mgL-1) were performed considering four temperatures (20, 30, 40 and 50°C), under 120 rpm shaking. Regarding temperature of 30°C and shaking of 120 rpm as suitable to improve the removal of Dowex Optipore SD-2 adsorbent, batch equilibrium adsorption experiments were carried out at pH values ranging from 1 to 12 and considering dye solutions with concentration varying from 5 to 300 mg L-1. From pcz results, pH values between 4 and 10 have evidenced electrically neutral behavior on adsorbent surface. Adsorption kinetic data were interpreted according to film diffusion, superficial adsorption and pores diffusion kinetic models. Six isotherm models such as Langmuir, Freundlich and Temkin were used to describe the equilibrium data, being the Langmuir isotherm fitted better to the data with a maximum adsorption capacity (qmax) of 315 mg L-1. Performing a comparison with other adsorbents, such as orange peel, macrophyte Egeria Densa, eggshell and activated charcoal reported in literature for reactive dye removal, the Dowex Optipore SD-2 adsorbent exhibits greater adsorption capacity than the other ones, being more effective for reactive dye removal, but with a slow kinetic response.